THE PSYCHODYNAMIC ANALYSIS OF TRAUMA SUFFERED BY ARCHER HALE IN MIA SHERIDAN’S ARCHER’S VOICE - Fiona Smith, Marion; Salsabila, Shafa; Kartiningsih, Rindrah; Utungga Pasopati, Rommel (TANDA, 2023)
This research is a study of Mia Sheridan’s novel Archer’s Voice. The purpose of this study is to reveal the trauma suffered by the mute male main character named Archer Hale. Archer was only seven years old when he got into a tragic accident that took away his voice and left him mute. He is a survivor of his own trauma since no one seems to care about him and his muteness. He was all alone, had no one to talk to, was an outcast in his town, and people called him a freak. Trauma is happened from a disturbing event that overwhelmed an individual and affects mood, motivation, and relationship in life. This feeling caused an individual to build a wall around and shut everybody out of life. Then, how is trauma suffered by Archer Hale portrayed in Mia Sheridan’s Archer’s Voice? Using qualitative method, this research is reviewed with Psychodynamic Theory focusing on psychological drives within individuals that explain human behavior and personality. In conclusion, Archer’s trauma has taken control of his life so bad that made him lose his voice both physically and mentally.